Rainbow Connection Number and Chromatic Index of Rough Ideal based Rough Edge Cayley Graph - Praba, B.; Obilia, X.A. Benazir (International Journal of Engineering and Technology, 2018)
Rainbow connection number and chromatic index are two significant parameters in the study ofgraph theory. In this work, rainbow connection number and chromatic index of Rough Ideal basedÂ Rough Edge Cayley Graph G(T(J)) are evaluated. We prove that the rainbow connection number of G(T(J)) is 2 and the chromatic index of G(T(J)) is 2(2n^m)(3m^1):Rainbow connection number and chromatic index are two significant parameters in the study of graph theory. In this work, rainbow connection number and chromatic index of Rough Ideal based Rough Edge Cayley Graph Â are evaluated. We prove that the rainbow connection number of Â is 2 and the chromatic index of Â is .